Áfricas: processos educativos presentes no terno de congada chapéus de fitas - Souza, Tatiane Pereira de (2012)
This study, entitled, "Africas: educational processes present in ―Terno de Congada Chapéus de Fitas‖ seeks to identify and understand the educational processes that are own of olders and youngers` participation in Terno de Congada Chapéus de Fitas, located in the city of Olympia-SP. These objectives are guided by the following research question: What learn from each other youngers and olders practitioners of Congada? Theoretical references which explains the ways and understandings in this research are located in a sociopolitical context: the African World - Africa and the Diaspora - and Latin America, not excluding the possibility of dialogue with other world views and perspectives, such as indigenous, European and Asian matrix. Theoretical discussions addressing insights and understandings about: social practices and educational processes; contributions to understanding the culture - the culture of African origin - interculturality, identity and ethnic-racial belonging, education of African origin, and its consequences on learning-teachinglearning -teaching as an ongoing process of educating themselves and educating between people. This study was conducted through a qualitative research approach, adopting the comprehensive observation and in-depth and individual conversations as methodological procedures, organized and analyzed with the phenomenology principles. The analysis and interpretation of data were made in the form of comprehensive description, revealing the educational processes that involve the faith, devotion, strength, respect for the older, family, inspiration, strength, identity, sense of belonging, joy, spirituality, the experience of the sacred, the collaborative partnership, ways to resist and survive the hardships, discrimination and prejudices, learning and teaching between older and younger that are useful as ways of living and living in the Congada and in the society. Therefore, the social practice of Congada not only celebrates the sacred, ancestral, but also teaches to celebrate life.